2020
DOI: 10.3389/fmicb.2020.01327
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Geochemical Dynamics of an Aquifer Stimulated for Microbial Induced Calcite Precipitation (MICP)

Abstract: Microbially induced calcite precipitation (MICP) is an alternative to existing soil stabilization techniques for construction and erosion. As with any biologically induced process in soils or aquifers, it is important to track changes in the microbial communities that occur as a result of the treatment. Our research assessed how native microbial communities developed in response to injections of reactants (dilute molasses as a carbon source; urea as a source of nitrogen and alkalinity) that promoted MICP in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…That approach lacks the selective pressure inherent to the dynamic chemical conditions and repeated washout–regrowth cycles employed here and expected during in situ stimulation field applications. A recent field study, in which an aquifer was stimulated with dilute urea (8–64 mM) and molasses (0.13–1.11 g L −1 as a carbon and energy source), showed little evidence that ureolytic bacterial populations were enriched to the extent required to precipitate native divalent cations as carbonates . Despite observed increases in ureC copy number, no measurements of urea or ureolytic activity were presented, nor were notable cations or carbonate content directly quantified.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That approach lacks the selective pressure inherent to the dynamic chemical conditions and repeated washout–regrowth cycles employed here and expected during in situ stimulation field applications. A recent field study, in which an aquifer was stimulated with dilute urea (8–64 mM) and molasses (0.13–1.11 g L −1 as a carbon and energy source), showed little evidence that ureolytic bacterial populations were enriched to the extent required to precipitate native divalent cations as carbonates . Despite observed increases in ureC copy number, no measurements of urea or ureolytic activity were presented, nor were notable cations or carbonate content directly quantified.…”
Section: Results and Discussionmentioning
confidence: 99%
“…A recent field study, in which an aquifer was stimulated with dilute urea (8−64 mM) and molasses (0.13− 1.11 g L −1 as a carbon and energy source), showed little evidence that ureolytic bacterial populations were enriched to the extent required to precipitate native divalent cations as carbonates. 42 Despite observed increases in ureC copy number, no measurements of urea or ureolytic activity were presented, nor were notable cations or carbonate content directly quantified. Additionally, the stimulated suspended communities bear little resemblance to those seen here or elsewhere, with only one transient appearance of substantial Firmicutes in a single sample (29%), the rest being composed primarily of Proteobacteria with minute Firmicute abundance.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the complexity of the natural environment, some phenomena are difficult to explain. Ohan et al [106] found that after applying MICP, the pH value of groundwater decreased, which contradicted the normal pH value increase.…”
Section: Models For Predicting the Curing Process Of Micp In The Fieldmentioning
confidence: 97%
“…e influence of the concentration of Ca 2+ and reaction time on the morphology and polymorph of CaCO 3 crystals was researched to reveal the mechanism of MICP [26]. e combination of glutinous rice slurry and calcium carbonate can further strengthen the mechanical properties of soil [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%